Using the ‘Circle of Care’ to Strengthen Families for Their Reintegration After Transition Away from Institutional Care - Kalra, Gurneet Kaur; Modi , Kiran (Asean Social Work Journal, 2025)
A safe family environment is held the best place for children to grow to their full potential. However, it has been observed that there has been an increasing trend in children without parental care still living in Child Care Institutions (CCI), although majority of them having one or both parents living and could be easily reunited. The Supreme Court’s Directive to the CCIs during the Covid-19 pandemic to send children living with them back to their families in an attempt to prevent the spread of the virus amongst children, saw many children being reunited with their families. But the reintegration proved to be a challenge for both the children and their families during this crisis. The efforts of the organisation Udayan Care in this regard, led to the initiation of the family strengthening project FiT, Families Together in the year 2021, to assure effective reintegration of the restored children with the families and to prevent their re-separation. The paper discusses provides an overview of the on-ground practices, its evidence-backed framework for re-integration, the Circle of Care approach and the necessary interventions under different domains, while also sharing some of the case studies from the project beneficiaries highlighting the impact of the inclusive care approach.